Editor's Introduction - Hallett, Michael A. (Social justice, 2018)
An introduction is presented which introduces the theme of the special issue, criminal justice in the U.S., and cites articles in the issue on topics including felony disenfranchisement, the needs of women prisoners in re-entry programming, and the growth of Christian post-secondary education in U.S. prisons.